ANALISIS HUKUM TERHADAP PERLINDUNGAN HUKUM BAGI INVESTOR DARI PRAKTEK WINDOWS DRESSING OLEH EMITEN DI PASAR MODAL - Julia Agnetha Br. Barus; Bismar Nasution; Budiman Ginting; Mahmul Siregar (Universitas Sumatera Utara, 2016)
ABSTRACT Information disclosure is an important element for the corporate world because information on the substance presents the description, notes or description of good for the State of the past and the latest of an enterprise and the market effect. But in reality, not all issuers disclose information that is actually about the fact material in the prospectus. If there is a breach of the principle of disclosure by issuers then issuers will be subject to administrative sanctions in accordance with Article 102 of The Capital Market Laws, namely in the form of a written warning, fines, namely the obligation to pay a certain sum of money, restrictions on business activities, freezing of business activities, business license revocation, cancellation of agreement and cancellation of registration. is an action that beautify the financial statements of a company. This is referred to as windows dressing. Windows dressings aims to enhance your company's image so as to attract investors to make investments. The practice of dressing the windows in the capital markets can still be said to be a reasonable course of action throughout the activities aimed to improve the company and not to the detriment of others. However, the practice of dressing the windows can be categorized as a criminal offence the capital markets if such activity creates information or issues misleading so as to affect the market mechanism. In the event of the occurrence of the windows dressing, the practice of legal protection afforded to investors could be done in a preventive and repressive. Preventative legal protection carried out by PT. Stock Exchange by doing a temporary suspension against securities trading. While the repressive legal protection carried out by OJK with conducting surveillance, investigation and the imposition of sanctions to any party proven to engage in the practice of cheating or fraud in the capital market. In addition, investors who feel aggrieved may do a lawsuit to the Court against the issuers that have been doing practice windows dressing. Keywords: windows dressing, investors, issuers.